Separate Identification of the Chinese Renminbi in the COFER Survey. (Policy Papers; Policy Paper ;, 2016)
Following the recent Executive Board decisions on the determination of the renminbi (RMB) as a freely usable currency, effective October 1, 2016, and its inclusion in the SDR basket on the same date, STA intends to separately identify the RMB in the survey on Currency Composition of Official Foreign Exchange Reserves (COFER) beginning with the survey for the fourth quarter of 2016. Consistent with staff's commitment to consult the Executive Board before separately identifying additional currencies in the COFER survey, this paper sets out the key considerations for the envisaged inclusion of the RMB in the COFER survey.